Lysis of Bacterial Cell Walls by an Enzyme Isolated from a Myxobacter - Ensign, J. C. (1965)
Ensign, J. C. (University of Illinois, Urbana), and R. S. Wolfe. Lysis of bacterial cell walls by an enzyme isolated from a myxobacter. J. Bacteriol. 90:395–402. 1965.—An exoenzyme which lyses intact cells, heat-killed cells, and cell walls of Arthrobacter crystallopoietes was purified 60-fold from the growth liquor obtained from a myxobacter (strain AL-1). The lytic enzyme was produced during growth of the organism in a number of complex media, the maximal amount of enzyme being produced in yeast extract broth. The purified enzyme lysed at different rates a number of gram-positive bacteria. With the exception of Rhodospirillum rubrum, Spirillum itersonii, and S. serpens, the gram-negative bacteria tested were not attacked.